2012
DOI: 10.1155/2012/949586
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Siblings of Individuals with Autism Spectrum Disorders

Abstract: The purpose of this study was to explore the experiences of siblings of individuals with autism spectrum disorders (ASDs) and identify their self-reported support needs. We conducted in-person semi-structured interviews with 12 siblings aged 7 to 15 of children aged 6 to 15 with ASDs. Employing a qualitative collective case study research method, we conducted cross-case analyses to address our research questions. Three major themes emerged: (a) descriptions of the sibling subsystem (b) cohesion between and amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
77
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 41 publications
3
77
0
2
Order By: Relevance
“…This expectation has been seen in some studies to have been present in childhood and adolescence, demonstrating anticipation of a future care role (Wilson 2011;Angell et al 2012). Futures planning is seen to be an area of difficulty within the literature (Mansell & Wilson 2010;Taggart et al 2012) and adult siblings have reported particular concern for the time when parents are no longer available to provide support (Benderix & Sivberg 2007;Orsmond & Seltzer 2007), and worry about financial, legal and care arrangements (Rawson 2009;Atkin & Tozer 2011).…”
Section: Introductionmentioning
confidence: 98%
“…This expectation has been seen in some studies to have been present in childhood and adolescence, demonstrating anticipation of a future care role (Wilson 2011;Angell et al 2012). Futures planning is seen to be an area of difficulty within the literature (Mansell & Wilson 2010;Taggart et al 2012) and adult siblings have reported particular concern for the time when parents are no longer available to provide support (Benderix & Sivberg 2007;Orsmond & Seltzer 2007), and worry about financial, legal and care arrangements (Rawson 2009;Atkin & Tozer 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Recently published studies have examined not only quantitative measures of mental health in siblings, but also their subjective experiences and perceptions (Petalas et al 2012; Shivers et al 2012; Angell et al 2012). Furthermore, study of the “broader phenotype” of autism traits has consistently shown that siblings of children with autism exhibit behavioral deficits in social, communication, and learning domains (see Dawson et al, 2002, for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Although research tends to focus on the negative aspects of having a sibling with ASD, NT siblings have reported many positive aspects and experiences of being raised with a sibling with ASD (e.g., Angell et al, 2012;Foden, 2007). Researchers found that having a sibling with ASD led to positive personality characteristics, such as higher levels of empathy and patience (Angell et al, 2012;Stalker & Connors, 2004).…”
Section: Positive Experiencesmentioning
confidence: 99%
“…Although research tends to focus on the negative aspects of having a sibling with ASD, NT siblings have reported many positive aspects and experiences of being raised with a sibling with ASD (e.g., Angell et al, 2012;Foden, 2007). Researchers found that having a sibling with ASD led to positive personality characteristics, such as higher levels of empathy and patience (Angell et al, 2012;Stalker & Connors, 2004). NT siblings also show increased awareness in recognising when their sibling is sad, frightened, and frustrated, which leads to higher levels of understanding and sympathetic behaviours (Benderix & Sivberg, 2007).…”
Section: Positive Experiencesmentioning
confidence: 99%
See 1 more Smart Citation